ANTIOXIDANT AND CYTOTOXIC ACTIVITIES OF ARECA CATECHU SEED EXTRACT IN SWISS ALBINO MICE USING EAC CELL LINE IN DIFFERENT CULTURE MEDIUM - DAS, SOURAV; MUKHERJEE, SENJUTI; CHOUDHURY, SANGEETA; BOSE, ANIRBANDEEP; ROY, SUKANTA (International Journal of Current Pharmaceutical Research, 2020)
Objective: Areca nut is the dried ripe seeds of Areca catechu, belonging to family Palmae. Areca nut contains a number of alkaloids, belonging to pyridine and piperidine groups, derived from amino acid lysine. Arecoline a nicotinic acid-based alkaloid present which exerts sialagogue property. But the habit of chewing marketed gutka may cause oral leukoplakia, sometimes lead to squamous cell carcinoma. However, Based on the phytochemical compounds present, it is predicted that it must show antioxidant and may show cytotoxic activities. Methods: The antioxidant activity (nitrite scavenging and hydrogen peroxide scavenging) and cytotoxic activity in two different medium were checked in EAC cell line using the swiss albino mice model. Results: The study was also postulated an idea about the qualitative and quantitive analysis of Areca catechu. The plant extract showed good Nitrite and Hydrogen peroxide scavenging activity. The cytotoxicity study conducted in swiss albino mice, cell viability and IC50 value was checked. The cytotoxic activity of different concentrations of different fractions of plant extract was checked in two different medium, i.e., PBS and RPMI 1640. IC50 values for following fractions which were studied in PBS; as, 91.73±73 (µg/ml), 183±36.24 (µg/ml), 53.74±1.562 (µg/ml) for crude ethanolic extract, alkaloid fraction and flavonoid fraction respectively. IC50 value in RPMI 1640 medium obtained as; 44.18±1.09µg/ml, 54.27±0.2279µg/ml and 51.24±2.461µg/ml for crude ethanolic extract, Alkaloid and Flavonoid fraction, respectively. Conclusion: Areca nut extract showed good scavenging activity depending on concentration. Relatively RPMI 1640 medium showed better cytotoxic activity than other mediums.